Government's role in the development of the venture capital industry : with special reference to Singapore - Ang, Siok Har (2008)
The purpose of this research is to study the venture capital industries in the various countries: the United States, Taiwan, Singapore, etc, with emphasis on Singapore. It aims to shed light on the role of the government when it comes to promoting venture capital in these countries.